T'ma v kontse tunnelia. Chast' 1 . T'ma v kontse tunnelia. Chast' 1 . Darkness at the End of the Tunnel. Part 1 . Тьма в конце туннеля. Часть 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with writer IUrii Nagibin. Featured in the program: Nagibin, IUrii Markovich (Writer) Contributors: Luchai, Galina (Anchor) Интервью с писателем Юрием Нагибиным. В программе участвуют: Нагибин, Юрий Маркович (Писатель) Создатели: Лучай, Галина (Ведущий/Ведущая)